Maintenance of long-term memory storage is dependent on late posttraining Egr-1 expression - Katche, Cynthia Lorena (2012)
Expression of immediate-early genes, like Egr-1, has been shown to be induced by activity-dependent synaptic plasticity or behavioral training and is widely thought to play an important role in long-term memory (LTM) formation. However, little is known about the role of Egr-1 in the maintenance of memory storage. Here we show that dorsal hippocampal Egr-1 protein expression is upregulated between 12 and 24 h after strong inhibitory avoidance (IA) training in rats. Local infusion of antisense oligodeoxynucleotide (ASO) to specifically knockdown Egr-1 in the dorsal hippocampus 8 h posttraining impairs LTM tested 7 days, but not 1 day after training, indicating that a delayed learning-associated expression of Egr-1 is necessary for the persistence of LTM storage. In addition, we show that consolidation of the IA memory is accompanied by an increase in Egr-1 protein levels 3 h, but not immediately or 1 h after training. Local infusion of egr-1 ASO 30 min before training in the dorsal hippocampus persistently hinders memory formation measured 1 and 7 days after IA training, indicating the crucial role of Egr-1 in memory formation. Our findings demonstrate that there are at least two waves of Egr-1 expression in the dorsal hippocampus after IA training, an early wave which is involved in IA LTM formation, and a lasting late wave that peaks around 12?24 h after a strong training protocol which is specifically involved in the maintenance of LTM storage.